Coronary embolism causing acute myocardial infarction. Review of the literature - Zachura, Małgorzata; Piątek, Łukasz; Kurzawski, Jacek; Janion, Marianna (Medical Studies/Studia Medyczne, 2016)
Coronary artery embolism (CE) should be considered as a nonatherosclerotic cause of acute myocardial infarction (AMI), especially in patients with conditions favouring the formation of intracardiac thrombi. The main aetiologies of CE have changed in recent decades. Currently, atrial fibrillation is the most common cause. Most studies on CE infarcts are case reports with small numbers of patients. There are still no clear guidelines for the management in embolic myocardial infarction. Depending on the aetiology, the treatment needs to be tailored individually. As long-term outcomes indicate, patients with CE causing AMI are at high-risk and therefore require close follow-up.